Desain Re-grouping dan Penjadwalan untuk Efisiensi Pemakaian Energi listrik - Muafa, Ahsan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
After the learning process in class is over, students tend to neglect leaving the lecture hall without turning off the lights and other electronic equipment. The student neglect causes a waste of electricity consumption. So that waste does not occur, it is necessary to regulate the use of electrical energy. It is required to separate electrical installations into groups that must be on for 24 hours and re-grouping lights that must only be on when needed. By dividing the time when electrical equipment is turned on, we can adjust the amount of electrical energy consumption. The method used is re-grouping the lamp installation, scheduling of the lighting, and remote control. The re-grouping activity was carried out by dividing lamp installations that needed to be on for 24 hours in one lane and lamp installations as required in several other lines. Meanwhile, to make the on-and-off effective, a remote control is needed, which allows the lights of this group to be turned on from a control room or even turned on from a smartphone.